Managing bifurcations: are two stents better than one?. (14th October 2021) - Araujo Leite Medeiros, P; Braga, C; Campos, I; Oliveira, C; Pires, C; Flores, R; Mane, F; Silva, R; Costa, J; Marques, J; Braga, C
Abstract: Introduction: Bifurcation percutaneous coronary intervention (PCI) is associated with a higher degree of complexity when compared with non-bifurcation procedures. Although 1-stent PCI remains the standard approach for most bifurcation lesions, data is constantly being published on 2-stent PCI. Aim: To evaluate and compare the characteristics and outcomes of patients that underwent bifurcation PCI with one or two stents. Methods: Single center, retrospective observational study including all patients who underwent bifurcation PCI between January 2015-December 2018. We defined two groups: 1-stent PCI group (1s-PCI) and 2-stent PCI group (2s-PCI). The 2s-PCI group included PCI patients with all the different techniques used in our center: provisional stenting with 2 stents, Cullote, crushing stent and DK Crush. Results: 1s-PCI group included 376 individuals and 2s-PCI group included 26. Overall baseline clinical characteristics were balanced between groups. There was no statistically significant difference in age (mean 64 vs 66; p=0.388), gender (79% vs 85% males; p=0.622) and comorbidities (hypertension, diabetes mellitus, hypercholesterolemia, chronic kidney disease, smoking and previous history of coronary artery disease). Also, there was no difference in clinical status (NSTEMI 36% vs 38%; stable disease 32% vs 42%; STEMI 28% vs 19%; unstable angina 5% vs 0%; p=0.419). Coronary angiography and lesion distribution were similar in both groups (p=0.367). However, radiation dose (median 90.5 [IQR=79] vs 156 [IQR=84] mGy cm 2 ; p<0, 001) and contrast volume (median 150 [IQR=100] vs 156 [IQR=83] ml; p<0, 001) were significantly higher in 2s-PCI group. At 12-month follow-up, mortality rate was higher in 1s-PCI group, but without statistical significance (8% vs 4%; p=0.71); the same is true for acute myocardial infarction at 12 months (3% vs 0%; p=0.368). Target-lesion failure was only reported in 4 patients in the 1s-PCI group. Survival tests showed no significant difference between groups (χ 2 (1, n=402)=0.634; p=0.426). Conclusion: Individuals that underwent 1s-PCI were overall similar to those who underwent 2s-PCI. Predictably, deploying more than 1 stent required more contrast volume and implied a higher radiation dose. We should note that our studied is greatly limited by the 2s-PCI group size, which may justify the lack of difference in the evaluated outcomes. FUNDunding Acknowledgement: Type of funding sources: None.